Field Performance of Surtreat TPS a Surface Applied, Penetrating Corrosion Inhibitor (FHWA-OK 04(04)) - (:unkn) unknown (My University, 2004)
Surtreat TPS penetrates into the PCC structure being treated, reacting with the cement phase of the concrete to increase hardness and compressive strength, decrease permeability and render the concrete inert to attack and penetration by acids, bases and other aggressive chemical solutions.
Keywords: Corrosion inhibitor; existing structures; reinforcing steel